2020
DOI: 10.1021/acs.jafc.9b07531
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticle-Infused Cotton Fiber: Durability and Aqueous Release of Silver in Laundry Water

Abstract: Although the application of silver nanoparticles to commercial antibacterial items is well-established, there have been increasing concerns that such particles might leach out, particularly into laundry water from textile products. A recently developed process wherein silver nanoparticles are synthesized in situ within the cotton fiber itself promises, however, to achieve the desired washing durability. In this study, the silver release behavior of the silver nanoparticle-infused cotton fabric during consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 42 publications
0
11
2
Order By: Relevance
“…The studies by El-Ra e et al showed that the addition of adhesives can improve washing durability, the AgNPs retention rate reached 65.8% after 20 washing cycles (El-Ra e et al 2014b). Although Nam et al(Nam et al 2020) and Zhang et al(Zhang et al 2013) improved the process to improve the durability of AgNPs on cotton fabrics, silver retention rate reached 67.0% and 81.5% after 20 and 30 washes, respectively, but the retention rate was still lower than that of our samples. The AgNPs loaded on our samples were wrapped inside the ber, resulting in its strong washing resistance.…”
Section: Slow-release and Wash-resistance Of Agnps On Fabricscontrasting
confidence: 58%
“…The studies by El-Ra e et al showed that the addition of adhesives can improve washing durability, the AgNPs retention rate reached 65.8% after 20 washing cycles (El-Ra e et al 2014b). Although Nam et al(Nam et al 2020) and Zhang et al(Zhang et al 2013) improved the process to improve the durability of AgNPs on cotton fabrics, silver retention rate reached 67.0% and 81.5% after 20 and 30 washes, respectively, but the retention rate was still lower than that of our samples. The AgNPs loaded on our samples were wrapped inside the ber, resulting in its strong washing resistance.…”
Section: Slow-release and Wash-resistance Of Agnps On Fabricscontrasting
confidence: 58%
“…In addition, AgNPs can penetrate into the multi-scale micropore of cotton ber and be stabilized inside the ber. Nam et al treated cotton bers with an alkaline solution to generate nanosized micro brillar channels, which were then introduced with [Ag(NH 3 ) 2 ] + ions and reduced to AgNPs.The AgNPs was successfully diffused into the interior of the cotton ber, and the washing resistance of the ber was greatly improved (Nam et al 2020). Montes-Hernandez et al put cotton fabrics in silver nitrate solution, and the silver ions were reduced to AgNPs, FE-SEM results of ber cross section show AgNPs diffused the interior of ber (Montes-Hernandez et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous studies have shown that the Ag NPs are well secured within the cotton fiber and are resistant to NP leaching even under aggressive agitation, losing less than 20% of their overall Ag content after 50 laundering cycles. Due to the mild reaction conditions (room temperature and mild mixing by magnetic stirring) it is expected that the catalyst maintains its high silver loading for the lifetime of the fiber [ 36 , 48 , 49 ], as confirmed by the lack of change in the UV/vis spectrum of the Ag NP–cotton catalyst after 10 cycles ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%